SPEECH RECOGNTION AND FALL DETECTION OF DOWN SYNDROME PEOPLE - sreenadh,; sivagami, Arasu (International Journal of Psychosocial Rehabilitation, 2020)
Down syndrome is the common disease in the world. Due to the additional copy of 21st chromosome this particular disease will be occurring. Another name of this disease is called trisomy. For this reason the children mental and physical development is going to delay. Most of the persons affected in their entire life. But each and every people are interested to live strong and satisfying their lives. Current communication technology also plays an important role in the medical field. Many service oriented organizations help the people with Down syndrome and provide more opportunities. Fall identification and sound detection of the Down syndrome people is the most important challenge in medical field. This paper proposed a new framework to fall and sound identification using wireless techniques. The proposed system will be monitor activates and voice of the Down syndrome people. In this system uses two sensor data identify and recognize the fall. The sound sensor is used to detect the voice of the people and transfer the message to the concern taker through GSM module.